2020
DOI: 10.1155/2020/5019607
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gender Authorship and Collaborations: A 30-Year Comparative Bibliometric Analysis of Manuscripts from The Journal of Bone and Joint Surgery and The Bone and Joint Journal

Abstract: Publishing original peer-reviewed research is essential for advancement through all career stages. Fewer women than men hold senior-level positions in academic medicine and, therefore, examining publication trends relative to gender is important. The goal of this study was to examine and compare publication trends in The Journal of Bone and Joint Surgery (JBJS) and The Bone and Joint Journal (BJJ) with a particular emphasis on trends regarding author gender. Data was collected and analyzed for manuscripts publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For example, we suspect increased expectations on trainees for research production in obtaining residency and fellowship positions might be potent drivers of authorship inflation. While a prior unpublished pilot study did not find a geographic origin to be associated with author count in this journal, geographic differences have been found in other journals 26 . Further studies to evaluate the impact of variables such as trainee authorship and source of origin would be of interest.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…For example, we suspect increased expectations on trainees for research production in obtaining residency and fellowship positions might be potent drivers of authorship inflation. While a prior unpublished pilot study did not find a geographic origin to be associated with author count in this journal, geographic differences have been found in other journals 26 . Further studies to evaluate the impact of variables such as trainee authorship and source of origin would be of interest.…”
Section: Discussionmentioning
confidence: 62%
“…While a prior unpublished pilot study did not find a geographic origin to be associated with author count in this journal, geographic differences have been found in other journals. 26 Further studies to evaluate the impact of variables such as trainee authorship and source of origin would be of interest.…”
Section: Limitationsmentioning
confidence: 99%
“…One way to measure scientific productivity is performing bibliometric studies, which are popularized in all scientific fields in general and the medical field in particular [ [14] , [15] , [16] ]. Previous studies reported a profound deficiency in publications on joint arthroplasty from Africa, while publications from Asian countries, although increasing in number, still lag behind those from North America and Europe [ 6 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%